Problems of universal manual work education in quarterly "Manual Workin School" (1927-1939) - Alicja Lisiecka (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
In the interwar years, the Polish pedagogical press experienced intense development. Numerous periodicals devoted to the issues of general, secondary and vocational education, periodicals about non-school education and methodical and subject writings were published. One of the recognized methodological writings was "Manual Work at School" (1927-1939). In the quarterly was discussed the broadly understood problem of teaching manual works in general schools: the issue of the impact of manual work on student development, methodological solutions were presented both in theoretical and practical terms, and the relationship between the subject and aesthetic education and other classes taught at schools was pointed out. Numerous numbers contained reports on conventions, exhibitions and conferences taking place in Poland and abroad. The quarterly presented deliberately selected articles supporting teachers' self-education. A permanent group of specialists in their articles addressed a wide range of topics: from the scientific organization of the teaching process through art to the automotive industry. Texts posted in "Manual Work at School" became a contribution to the discussion and reflection on the organization of education.